A unique case of herpetic keratitis manifesting as recurrent preseptal cellulitis - Emily Miller; Maxwell Ward; Tasaduq Fazili; Ekta Bansal (IDCases)
Preseptal cellulitis is typically caused by nasopharyngeal bacteria and can usually be treated with empiric antibiotics. We present a case of herpes simplex virus (HSV) 1 keratitis manifesting as recurrent and treatment refractory preseptal cellulitis. This is a rare presentation that is infrequently reported in the literature. Due to the potential for permanent vision loss, it is important to consider herpes viruses as an etiology in immunocompromised patients with preseptal cellulitis not responding to standard treatment.